Evaluation IT Goverment Capabilities of the Facematch RIM Polri Recruitment System Using the COBIT 5 Framework - Iswara, Made Wikrama Dana; Anggraeni, Sita (Jurnal Teknik Informatika (Jutif), 2025)
One of the technology implementations used by the Government, especially the latest POLRI in the Facematch RIM POLRI system in the recruitment of POLRI new members, has been designed to prevent fraud in the Police recruitment process by recording the faces of prospective members as a valid identity. To determine the capabilities of this system, qualitative data collection was carried out through interviews with related parties and observation of overall system governance activities. The operational implementation of this system has several findings, including the recording process and image quality monitoring mechanism, the continuity of the capture process, to network and infrastructure constraints. The findings are mapped within the COBIT 5 framework domain to determine the gap for improvement in Acceptance System Governance based on Facematch RIM POLRI at POLRI.  These findings can contribute to the improvement of IT Governance practices in the POLRI Admissions System in Government in line with the COBIT 5 framework domains and are expected to provide strategic recommendations to overcome the challenges faced and improve the efficiency and effectiveness of the system in supporting organizational goals.